The Relationship between Knowledge and Attitude with the Implementation of Pregnant Gymnastics in Pregnant Women in Trisemester II and III at the Lubuk Linggau City Taba Health Center in 2023 - Handayani, Siska Ulan; Murwati, Murwati; Yulianti, Syami (Student Scientific Journal, 2024)
Pregnancy is the fertilization or union of a spermatozoa and an ovum followed by nidation or implantation. A normal pregnancy will last 40 weeks (10 lunar months or 9 months according to the international calendar). Pregnancy can be divided into 3 periods of approximately equal intervals (approximately 13 weeks or 3 months), which are known as trimesters I, II and III (Prawirohardjo, 2018). The purpose of the study was to find out the relationship between knowledge and attitudes with the implementation of pregnancy gymnastics in pregnant women in Trisemester II and III at the Lubuk Linggau City Taba Health Center in 2023 This type of research is analytical research using this type of research is analytical research using a cross-sectional design (Hidayat, 2012). The population in this study were all pregnant women in the second and third trimesters in the Taba health center area of Lubuk Linggau City in 2022, namely 391 people, the number of samples in this study were 80 respondents. The results of this study indicate that more than half of the respondents 42 (52.5%) were knowledgeable enough at Puskesmas Taba Lubuk Linggau City in 2023, most of the respondents 68 (85%) had a positive attitude at Puskesmas Taba Lubuk Linggau City in 2023, most of the respondents 70 (87.5%) did the implementation of pregnant gymnastics at Puskesmas Taba Lubuk Linggau City in 2023, There is a relationship between knowledge and the implementation of pregnant gymnastics at the health center taba lubuk linggau city in 2023, There is a relationship between attitudes and the implementation of pregnant gymnastics at the taba health center, Lubuk Linggau city in 2023 The results of this study are recommended to the health center to the health center to implement the pregnant gymnastics program, because pregnant gymnastics has many benefits for the health of pregnant women and smooth delivery and provide education about pregnant gymnastics.